Problems of Allocation of Consumer Loans in Commercial Banks - Ergasheva Zarifa Bakhtiyarovna (European Science Publishing, 2024)
This article examines the complexities and challenges associated with the allocation of consumer loans within commercial banks. By analyzing the literature, it examines the methods used, the results obtained, and discusses the implications. Conclusions from the discussion provide insights and suggestions for addressing these issues.
Keywords: Consumer loans, commercial banks, separation, problems, methods, results, discussions, conclusions, proposals.